Incorporation of the Endoplasmic Reticulum Stress-Induced Spliced Form of XBP1 mRNA in the Exosomes - Hosoi, Toru; Nakashima, Mieko; Ozawa, Koichiro (Frontiers in Physiology, 2018)
It is known that endoplasmic reticulum (ER) and nucleus communicate with each other to cope with ER stress. However, the mechanisms through which extracellular transmission of ER stress occurs remain unexplored. When the ER stress-induced unfolded protein response (UPR) is activated, the X-box binding protein 1 (XBP1) mRNA is spliced by inositol-requiring enzyme-1α (IRE1α) to produce the spliced form of XBP1 (sXBP1). In the present study, we found that sXBP1 mRNA in the cell may be incorporated into the exosomes and was released extracellularly. We found that the ratio of the mRNA levels of sXBP1 to unspliced XBP1 (uXBP1) in the exosome was higher than that of cells in MIN6 mouse pancreatic β cells. A similar effect was observed when XBP1 splicing was induced by overexpressing IRE1α in HEK293T cells. These results suggest that the incorporation of sXBP1 into the exosomes is a novel mechanism of UPR transmitted to extracellularly, which would be triggered when cells are exposed to stress.